Effect of Plant Spacing and Foliar Spraying with Vitamin C on Growth and Yield of Okra (Abelmoschus esculentus L.) - Hamid, Nadia Nasser (Journal of agricultural, environmental and veterinary sciences, 2020)
An experiment was conducted during the Agricultural spring seasons 2019 at Abul-Khasib, Basrah. The experiment included 6 treatments combination resulted from the interaction between two plant distances (30 and 60 cm apart), with the addition of three concentrations of vitamin C (0, 20, 40) Mg. liter-1. Randomized Complete Block Design was used in a factorial experiment, mean variations replication compared at 0.05. Results can be summarized as follows: The plant spacing of 60 cm caused a significant effect on the all of the results of vegetative growth (leaves number, surface leaf area, total soluble of carbohydrates contents and chlorophyll) except plant height it gave a significant increase in 30 cm. whereas, the plant spacing of 60 cm gave a significant reduction in the (fruit weight, fruit number. plant-1 and yield. plant-1). Regarding the spraying, levels increased significantly in all component, except pod length it gave a significant decrease in vitamin C levels increased. While there was no significant effect on the interaction between the two studied factors.